Green approach to the Isosorbide Conversion into Dimethyl isosorbide - Ginés-Molina, María José; Luque, Rafael; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2017)
Isosorbide is one of the most promising products derived from sorbitol. It has already found many applications, mainly in the polymer industry and medicine, such as isosorbide polycarbonate1 (DURABIO®) and isosorbide nitrates as vasodilator for angina pectoris2. The methylation of the two hydroxyl groups of isosorbide molecule gives rise to the formation of dimethyl isosorbide (DMI), which is a high boiling solvent (235ºC), used in skin care formulations because of its solubilising capacity and performance enhancing of many different topical skin actives3. Currently, DMI synthesis implies the use of methyl halides or dimethyl sulfate. A safer and more environmental benign approach has been proposed by Tundo et al4 by employing dimethylcarbonate (DMC) as both reactant and solvent in the presence of sodium methoxide. In the present work, the synthesis of DMI in an excess of DMC by using a MgAl mixed oxides (MgAlOx), as heterogeneous catalyst, under mild reaction conditions, is proposed.
Keywords: Química inorgánica - Congresos; Biomass; Dimethylisosorbide; Sorbitol; Dimethylcarbonate; Heterogeneous catalysis